The right of sovereignty : Jean Bodin on the sovereign state and the law of nations - Lee, Daniel, 1979- (Oxford : Oxford University Press, 2021)
Examining the origins of the principle of sovereignty in the legal and political thought of Jean Bodin, this book explores his creative synthesis of classical sources in philosophy, history and the medieval legal science of Roman and canon law in crafting the rules governing state-centric politics.
This edition also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 7, 2021).
Keywords: Sovereignty; Bodin, Jean, -- 1530-1596.